2003
DOI: 10.1002/ptr.1141
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant flavonoids and phenolic acids from leaves of Leea guineense G. Don (Leeaceae)

Abstract: From leaves of Leea guineense (Leeaceae) three hydrophilic flavonoids were isolated and identified as quercetin-3'-sulphate-3-O-alpha-L-rhamnopyranoside, quercetin-3,3'-disulphate and a new flavonoid sulphate, quercetin-3,3',4'-trisulphate, together with kaempferol, quercetin, quercitrin, mearnsitrin, gallic acid and ethyl gallate. The structures were established by spectroscopic analysis (UV, MS, (1)H-NMR, (13)C-NMR and 2D-NMR). Their antioxidant effect on free radical scavenging was evaluated in the DPPH ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Ethyl gallate and methyl gallate have been reported to possess other biological activities such as antioxidant effect on free-radical scavenging (Op de Beck et al, 2003) and relaxant effect in guinea-pig trachea in vitro by activation of large conductance Ca 2þ activated K þ channels (Paulino et al, 1999). The only report on the chemistry of the genus Talisia is about the isolation of isolectins from T. escualenta (Freire et al, 2001).…”
Section: Bioactivity Of Isolated Compoundsmentioning
confidence: 97%
“…Ethyl gallate and methyl gallate have been reported to possess other biological activities such as antioxidant effect on free-radical scavenging (Op de Beck et al, 2003) and relaxant effect in guinea-pig trachea in vitro by activation of large conductance Ca 2þ activated K þ channels (Paulino et al, 1999). The only report on the chemistry of the genus Talisia is about the isolation of isolectins from T. escualenta (Freire et al, 2001).…”
Section: Bioactivity Of Isolated Compoundsmentioning
confidence: 97%
“…Besides this, some sulfated flavonols, including quercetin and rutin, possess anticoagulant or antiaggregant activity and also substantial antiviral activity . Quercetin sulfates were shown to display some lipid peroxidation inhibitory effect and antiradical activity (in the 2,2‐diphenyl‐1‐picrylhydrazyl assay) . Quercetin 3′‐ O ‐sulfate demonstrated not only inhibition of cyclooxygenase‐2 activity but also reduction of the expression of cyclooxygenase‐2 messenger RNA .…”
Section: Introductionmentioning
confidence: 99%
“…[23] Quercetin sulfates were shownt od isplay some lipid peroxidation inhibitory effect [24] anda ntiradical activity (in the 2,2-diphenyl-1-picrylhydrazyl assay). [25] Quercetin 3'-O-sulfate demonstrated not only inhibition of cyclooxygenase-2a ctivity but also reduction of the expression of cyclooxygenase-2 messenger RNA. [26,27] Other interesting biological activities (antimicrobial, anti-inflammatory,a nti-HIV,a ntitumor,e tc.)…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemical study on the chemical constituents of this plant has not been reported. However, previous investigation of plants in the same genus reported the presence of flavonoids and phenolic acid [1][2][3]. The present paper deals with the isolation and structural determination of five compounds, including a new megastigmane diglycoside (1), as well as one known benzyl glycoside (2), two flavonol glycosides (3 and 4) and one megastigmane glucoside (5) from the leaves of this plant.…”
Section: Introductionmentioning
confidence: 96%